Gesture Based Pick and Place Robot - Visvesvaran C, Pavithra D, Raashiha S R, Ragasri R, Arthysri N, Janani R G and Keerthana Priya R (International Journal of Advanced Science and Technology, 2020)
Gesture recognition technology is used to identify human gestures with the help of mathematical algorithms. This technology recognizes the hand, tracks the hand movements and provides information about hand position orientation and flux of the fingers. In this paper we proposed a system using camera to capture gestures and by using image processing and machine learning, the captured gesture image is recognized, over which some actions are set. OpenCV is used for image processing, python as the programming language and microcontroller for the robot to pick and place the object.